DEEP LEARNING IN ISLAMIC RELIGIOUS EDUCATION: ENHANCING STUDENTS’ HIGHER-ORDER THINKING SKILLS (Pena Cendekia Insani, 2026)
This study aims to examine the strategies of Islamic Religious Education (PAI) teachers in implementing a deep learning approach to develop students’ Higher-Order Thinking Skills (HOTS) at SMP Muhammadiyah 5 Surakarta. This research employed a descriptive qualitative method. Data were collected through observations, interviews, and documentation and analyzed using the Miles and Huberman interactive model. The findings show that PAI teachers implemented several deep learning strategies, including discussion-based learning, problem-based learning, reflective questioning, and project-based assignments. These strategies encouraged active student participation and contextual learning experiences that helped students develop critical, analytical, and reflective thinking skills. The implementation of deep learning also contributed to improved learning outcomes and students’ ability to relate Islamic values to everyday life. The study concludes that the deep learning approach supports the development of HOTS in Islamic Religious Education through meaningful and student-centered learning practices.